Evaporative cooling photovoltaic panel in the conditions of a hot period - Isroil A. Yuldoshev; Farkhodjon Sh. Turaev; Bozorbek M. Botirov; Yunus M. Kurbanov; Dalira R. Kakharova; Jamshid B. Juraev (PROBLEMS OF ENERGY AND SOURCES SAVING, 2024)
Relevance: this paper presents the results of the development and field studies of "passive", namely, evaporative cooling of photovoltaic modules (PV) in climatic conditions of the city of Tashkent. The experiments were conducted in a Heliopolygon located on the territory of the Tashkent State Technical University named after Islam Karimov in Tashkent city. Geographical coordinates ( east longitude and north latitude). Theoretical calculations on the evaporative cooling of PV modules based on crystalline solar cells have been carried out. The data obtained show that evaporative cooling is really effective and can significantly reduce the loss of PV modules power from overheating. Aim: to increase the efficiency of PV modules based on crystalline solar cells due to evaporative cooling with a maximum decrease in the temperature of the working surface of the modules. Methods: during the PV modules experiment with an evaporative cooling device, standard methods of thermal engineering were used, including the method of "passive" cooling. Results: experiments to determine the efficiency of evaporative cooling were tested on two identical PV modules (one with cooling, the other without cooling) with an area of ~ 1.64 . At an ambient temperature of 38 , the working surface temperature of the cooled PV module steadily decreased to 33-35 , and the temperature of the non-cooled PV module reached 64 . At such temperatures, the decrease in the efficiency of the cooled PV modules is no more than 6%, and the non–cooled one is ~ 20%. The experiments showed good convergence of the PV modules temperature calculated from the heat transfer equations with experimental data.